'25‐Hydroxyvitamin D, Autoantigenic and Total Antibody Concentrations: Results from a Danish Case–control Study of Newly Diagnosed Patients with Childhood Type 1 Diabetes and their Healthy Siblings'. (12th December 2017) - Thorsen, S. U.; Pipper, C. B.; Johannesen, J.; Mortensen, H. B.; Pociot, F.; Svensson, J.
Abstract: B cells have recently entered the stage as an important accessory player in type 1 diabetes (T1D) etiopathogenesis. Experimental studies suggest regulatory functions of vitamin D on B cells. However, only a few human studies, with considerable methodological limitations, have been conducted within this field. Our objective was to investigate whether higher 25‐hydroxyvitamin D (25(OH)D) concentrations were inversely associated with β‐cell autoantigens glutamic acid decarboxylase (isoform 65) (GADA) and insulinoma‐associated antigen‐2A (IA‐2A). Further, we also wanted to examine the relationship between 25(OH)D and total antibody concentrations. We randomly selected 500 patients with newly diagnosed T1D and 500 siblings for 25(OH)D, antibody and genetic analysis from the population‐based Danish Registry of Childhood and Adolescent Diabetes. The relative change (RC) in the mean concentration of GADA, IA‐2A and antibody isotypes by a 10 nmol/l increase in 25(OH)D concentration was modelled by a robust log‐normal regression model. We found no association between 25(OH)D and GADA [adjusted RC per 10 nmol/l increase: 1.00; 95% confidence interval (CI): 0.98–1.02] and IA‐2A [adjusted RC per 10 nmol/l increase: 0.92; CI: 0.76–1.12]. Further, 25(OH)D was not associated with the total concentration of antibody isotypes [immunoglobulin (Ig)A, IgE, IgG and IgM]. All null findings were unaltered after adjustment for genetic variation in the vitamin D pathway. Physiological concentrations of 25(OH)D are unlikely to have a clinically important effect on antibody concentrations in a paediatric population of newly diagnosed patients with T1D and their healthy siblings.